Transformasi Akad Mudharabah dari Konsep Fikih ke Akad Perbankan - Nufi Mu'tamar Almahmudi (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2022)
Islamic banking is currently experiencing rapid development in Indonesia. However, in its application as a society, it still assumes that Islamic banking is just a label used to attract the sympathy of the Muslim community in the banking sector. Mudharabah contract is one of the products used in Islamic banking. This paper tries to present a description related to mudharabah contracts from classical to contemporary fiqh concepts and their application in Islamic banks using descriptive analysis methods. the precautionary principle is something that must be considered by banks in providing financing and funding, this principle requires Islamic banking to modify the concept of mudharabah, so that it can be applied and developed in today's banking world. As for the difference in the concept of a mudharabah contract from theory to practice, it can be seen in determining the profit-sharing ratio of the mudharabah, determining the contract period/period of the mudharabah, requiring collateral, and the party bearing the collateral.